Applying contextual integrity to digital contact tracing and automated triage for hospitals during COVID-19. (November 2021) - Martens, Marijn; De Wolf, Ralf; Vadendriessche, Karel; Evens, Tom; De Marez, Lieven
Abstract: To control and minimise the spread of COVID-19, various technological solutions have been proposed. In this research, we focus on digital contact tracing and automated triage for hospitals. We conducted an online survey in Flanders ( N  = 1708) to investigate the perceived appropriateness of these systems based on the Contextual Integrity framework, as developed by Nissenbaum [1]. For digital contact tracing, significant differences were found between the appropriateness of using various types of data for different goals. Precise individual location data (i.e. GPS) was considered to be least appropriate and much less appropriate than proximity data (i.e. Bluetooth) or coarser location data (i.e. GSM). Goals for digital contact tracing with a high individual impact were considered to be less appropriate than goals with a low individual or societal impact. In addition, the data showed that respondents would find the usage of digital contact tracing to be less appropriate after the pandemic, underlining the temporality of this technological solution. For automated triage, the results indicated that gender is perceived to be significantly less appropriate than the other types of data, including age, to determine the priority of treatment. Highlights: Individual data is less appropriate than population data for digital contact tracing. High individual impact goals are less appropriate than goals with a societal impact. The appropriateness to share data with digital contact tracing apps is temporary. Gender is less appropriate than other data to use to determine the priority of treatment.